Policy Challenges in the Gulf Cooperation Council Countries. (International Monetary Fund, 1996)
The Gulf Cooperation Council (GCC) countries face important policy challenges and opportunities. This paper covers the economic developments and policies since 1980; the impact of the GCC's external environment; the medium-term economic prospects; the broad outlines of a common adjustment and reform strategy, and the implications of adjustment in the GCC countries on the rest of the Middle East and North Africa region.